Reframing Eco-Literacy in Early Childhood Education: Policy–Practice Tensions and Pedagogical Recontextualization in Indonesia and Malaysia - Dewi, Anastasia Fransiska; Mustaji, Mustaji; Ningrum, Mallevi Agustin (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study examines how eco-literacy is conceptualised, institutionalised, and enacted in Early Childhood Education (ECE) in Indonesia and Malaysia, with particular attention to tensions between sustainability policy and classroom pedagogy.Design/methods/approach – A qualitative comparative design combined constructivist grounded theory with critical policy document analysis. data were generated through semi-structured interviews, classroom observations, and institutional document review in two purposively selected eco-oriented kindergartens: TK Agripina in Surabaya and Tadika EcoSmart in Johor Bahru. Analysis proceeded through iterative coding, constant comparison, and cross-case synthesis.Findings – Eco-literacy was enacted through three interrelated processes. First, routine environmental activities became pedagogically consequential only when teachers mediated them through dialogue, inquiry, and emotionally grounded reflection. Second, policy commitments to sustainability were only partially realised in practice because teacher capacity, pedagogical guidance, and curriculum integration remained uneven. Third, children’s ecological awareness developed through culturally mediated participation in which collective values, community engagement, and selective digital mediation shaped how environmental responsibility was understood.Research implications/limitations – This study theorises eco-literacy in ECE as a socio-reflective, culturally mediated, and policy-contingent process in Global South contexts. It proposes an interpretive Eco-Pedagogical Framework linking policy, teacher enactment, and socio-cultural mediation. However, its two-case qualitative design limits transferability; future research should adopt multi-site and longitudinal approaches.Practical implications – Effective eco-literacy implementation requires systemic alignment through strengthened teacher ecological competence, explicit pedagogical scaffolding, and institutional support for reflective practice, alongside culturally grounded and community-based learning integration.Originality/value – The study reconceptualises eco-literacy as a culturally situated process of pedagogical recontextualisation in Muslim-majority Southeast Asian ECE, offering a nuanced Global South perspective beyond technocratic models of sustainability education.Paper type Research paper